(untitled) (Journal of Computational Mathematics, 1992)
Based on the approximation of the linear operator semigroup, this paper proposes a simplified viscosity splitting method for solving the initial boundary value problems of the N-S equation. Some stability and convergence estimates of the method are proved. In particular, the mechanism of Chorin's method is explained and justified by the splitting method.